Diffusion under micro-gravity-Mass transfer from rising bubble in a stagnant fluid column - Bari, Md Ashfaqul; Akbulut, Cemil; Münsch, Manuel; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2018)
Numerical simulation of two‐phase flows using Volume of Fluid (VOF) method is known be to susceptible to parasitic currents, which arises due to erroneous interface curvature calculation to model the surface tension force. The interface curvature calculation scheme in OpenFoam has been modified according to the Sharp Surface Force (SSF) which reduced parasitic currents magnitude significantly. Alongside SSF method the Continuous Species Transfer (CST) equation is implemented in OpenFOAM 4.1 to simulate mass transfer from an Oxygen bubble to the surrounding stagnant water‐glycerol solution under micro‐gravity environmen
Keywords: Diffusion; Micro-gravity; OpenFOAM

Heat recovery optimization of a shell and tube bundle heat exchanger with continuous helical baffles for air ventilation systems - Bari, Md Ashfaqul; Münsch, Manuel; Schöneberger, Bastian; Schlagbauer, Bernhard; Tiu, Andrea Alina; Wierschem, Andreas (International Journal of Air-Conditioning and Refrigeration, 2024)
We report a numerical evaluation of the impact of continuous helical baffle on the heat recovery efficiency of counterflow tube bundle heat exchangers. The baffle inclination angle has been varied from 11 ∘ to 22 ∘ . Since the fluid flows over the tube bundle at an angle due to helical flow inside the shell, the heat exchanger operates in cross counter mode. Fluent simulations with the k- ω transition shear stress transport turbulence model have been performed to investigate the thermal-hydraulic parameters of the system in terms of heat recovery efficiency, pressure loss, and overall heat transfer rate. Outside air temperature has been varied to mimic cold and warm weather. Pressure loss has been constrained to be less than 250 Pa, conforming to EU guidelines for energy labeling of residential ventilation units. At the maximum volume flow rate of 40 m 3 /h, the device performed with over 80 % heat recovery efficiency for the considered temperature difference. Continuous helical baffles helped to improve convective heat transfer by reducing cross flow area and increasing velocity. Smaller angles result in greater pressure loss while having no discernible effect on heat recovery efficiency for the considered geometry. The analysis demonstrates the potential of a compact counterflowing recuperative heat exchanger with continuous helical baffles for decentralized ventilation systems and serves as a basis for further optimization.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Air to air heat exchanger; Compact recuperative heat exchangers; Continuous helical baffle; Cross-counter flow; Decentralized ventilation; Grid Convergence Index (GCI); k- ω transition SST